Voters Versus the Corpus of fictional POTUS - Cheng, R. (2015)
Scholars have argued that voting behaviour changes over time and, today, voters are no longer loyal to traditional ‘political brands’. We, hence, try to explore, through constructing ‘action corpora’ using novels, movies and TV dramas from the last 50 years (1960-2012) relating to fictional US presidents to see what the mass media have been conveying to the public subconsciously over time. We then looked at and discussed how people have responded since they last voted over the past five US presidential elections from 1992 through 2008 using excerpts from the Corpus of Contemporary American English (COCA). While voters were found to fall into two broad categories when making their voting decisions, powerful media bias right before elections could have caused vote swings and, hence, voters could have voted for ‘the wrong person with all the wrong reasons’ when, in fact, they were subconsciously warned – not by anyone else, but by the mass media.